Sedimentology and sequence stratigraphy of automated hydraulic flow units – The Permian Upper Dalan Formation, Persian Gulf. (January 2023) - Kakemem, Umid; Ghasemi, Mohammadfarid; Adabi, Mohammad Hossein; Husinec, Antun; Mahmoudi, Ayoub; Anderskouv, Kresten
Abstract: The Upper Dalan (Khuff-equivalent) Formation constitutes the principal reservoir of the giant gas fields in the Persian Gulf Superbasin. A sedimentological and sequence stratigraphic analysis was conducted on selected cores from the South Pars, Kish, and Lavan gas fields, offshore Iran, to evaluate a recently proposed method for automatic reservoir zonation, and discuss the predictability of such defined zones. The succession consists of nine evaporite-carbonate lithofacies grouped into three shallow-marine facies associations (shoal, lagoon, and tidal flat) that were deposited on a low-gradient homoclinal ramp. Lithofacies are stacked into two complete long-term (3rd-order?) transgressive-regressive depositional sequences. Sequence boundaries were defined by facies stacking patterns and presence of evaporites and meteoric diagenetic features. The reservoir quality was improved by both early-stage dolomitization and dissolution, whereas pervasive pore-filling anhydrite cementation, compaction, and late-stage over-dolomitization reduced the reservoir quality. Whereas dolomitization overall slightly affected porosity, it significantly increased the permeability in mud-dominated lithofacies. Fibrous and bladed calcite rim cements, as well as micritization of the grain-dominated lagoon and shoal lithofacies, prevented porosity reduction during the early- and late-stage burial by building a stronger framework. Core-plug porosity and permeability measurements were used to calculate the Winland R35, Reservoir Quality Index (RQI), and Flow-Zone Indicator (FZI) values. A novel, fully automated approach, was used to effectively identify the hydraulic flow units (HFUs). The HFUs are sedimentologically distinct units with characteristic combinations of the original rock texture and the subsequent diagenetic overprint, and their subsurface position within the sequence stratigraphic framework may be predicted. Highlights: Automated reservoir zonation yields four hydraulic flow units of Upper Dalan Fm. Succession has three facies belts with nine lithofacies that are stacked into 3rd-order sequences. Late transgressive system tracts are overall the most prolific hydraulic flow units. Spatial distribution of hydraulic flow units was predicted by sequence stratigraphy.